FROM DATA TO DECISIONS: A MODERN MARKETING MANAGER'S GUIDE - Alpizar; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
This article explores how modern marketing managers can effectively transform data into actionable decisions in an increasingly complex and data-rich environment. The rapid expansion of digital technologies has led to an explosion of data from multiple sources, creating both opportunities and challenges for organizations. While data offers valuable insights into customer behavior, market trends, and performance, many organizations struggle to convert this information into meaningful strategic actions. Using a narrative literature review, this study synthesizes insights from academic and industry sources to identify key themes in data-driven marketing, including data as a strategic asset, analytical capabilities, integration of data and intuition, and real-time decision-making. Based on these findings, the article proposes a “From Data to Decisions” framework consisting of four stages: data collection, data analysis, insight generation, and decision implementation. The study also highlights the critical role of technology, including analytics platforms, artificial intelligence, and automation, as well as the importance of managerial capabilities such as data literacy and cross-functional collaboration. The article contributes by bridging theory and practice and offers practical guidance for marketing managers navigating data-driven decision-making. However, further empirical research is needed to validate the proposed framework.